Kiat-Kiat Mengatasi Permasalahan Hukum Bagi Pelaku Usaha Kecil Mikro di Desa Pandeyan - Kurnianingsih, Marisa; Kuswardani, Kuswardani; Hartanto, Hartanto (Abdimas Indonesian Journal, 2024)
The development of micro small businesses must be directly proportional to legal knowledge for the perpetrators, because with the development of micro small businesses, the possibility of intersecting with legal problems will be even greater. Of course, all micro small business actors hope that their business is fine, but problems such as civil, criminal, labor, tax will not rule out the possibility of being experienced in the future. Of course, with a good level of knowledge, problems such as disputes or disputes can be avoided in the future or at least if disputes occur micro small business actors know how to overcome them. Evidence of the large number of civil problems in court is an indication that intentionally or unintentionally many business actors do not carry out rights or obligations so that disputes between micro small business actors are born. Tips for overcoming legal problems for micro small businesses aims to foster legal awareness and settlement procedures in the event of disputes in the future, the author feels the need to provide legal counseling for micro small businesses in order to foster knowledge and understanding related to tips on overcoming legal problems for micro small businesses for the realization of more advanced Indonesian micro small businesses.